(untitled) (E Conference Zone, 2022)
Vinyl chloride is one of the most important monomers, mainly for the production of polyvinylchloride, as well as for the acquisition of sopolimers with vinyl chloride, vinilatsetate, acrylonitril, methylmetakrilat, etc. It is also used in the extraction of vinyldenxloride and methyl chloroform [1]. The hydrochlorized vinyl chloride extraction of acetylene is characterized by the following reaction: СН≡СН+НСl→CH2=CHCl + 112,4 kj/mol (1) During the reaction, 1.1-dichloretan is produced. СН2=СНСl + HCl→CH3CHCl2 (2) Muvozanat konstantalarining temperaturaga bog’lanishi quyidagicha ifodalanadi: lgKp1=794/t+0.72 lgKp2=456/t-3,25 When the temperature is < 300oC (1), the reaction is almost irreversible. At 200°C, a small amount [at 0.12% mass 1 MPa] can be produced from 1,1 dichloretan, especially when pressure is increased.